TINGKAT KETERGANTUNGAN DALAM PEMENUHAN AKTIVITAS KEHIDUPAN SEHARI-HARI DENGAN HARGA DIRI PASIEN - Andriani, Yessi (Indonesian Journal of Nursing Health Science, 2018)
Stroke is the third largest discase after heart disease and cancer in Indonesia. Estimed 28,5% patiens of stroke are died and the balance have patial or total paralysis. Intake data from Nasional Stroke Hospital Bukittinggi found the incidence of recurrent stroke was 2 years has an increase in the number of incident cases of stroke behind the year 2012 and was 1816 cases and in 2013 was 1937 cases. The Purpose of the research is to determine the relationship of daily living activity with the price of self. Research using descriptive correlation design with analysis Chi-square test with cross-sectional approach. The research was conducted on 8 July â 8 Agust in Neurology Polyclinic Nasional Stroke Hospital Bukittinggi 2014. Population of this research are patiens of stroke who visiingt at Neurology Polyclinic Nasional Stroke Hospital Bukittinggi. Accidental sampling was used for sampling to 40 people. The instrument was index barthel and a questionnaire. Data processing and data analysis was done by computering processes. From this study it can be found that for 40 samples obtained 32,5% have medium dependence in daily living activity and 55% have low price of self. A statistical test Chi-square test p value = 0,002 means that Ho is rejected. So, the conclusion is daily living activity with the price of self on pasien of stroke in Neurology Polyclinic Nasional Stroke Hospital Bukittinggi 2014. It is expected to extension of daily living activity and price of self can be done directly through counseling or indirectly through media such as posters.Â Keywords: daily living activity, price of self, stroke